Il territorio rurale nel Piano Paesaggistico della Toscana: strutture, criticità e regole per le trasformazioni - Gisotti, Maria Rita (Scienze del Territorio, 2014)
What can be the role of a regional planning instrument in triggering the return to earth, the support for a recovery of agro-forestry practices and of the related economies? The Regional Landscape Plan of Tuscany, currently in draft, has worked so far in this direction by developing a corpus of description and guidance materials organised in a taxonomy of regional rural landscapes. The main descriptive paradigm is the rural morphotype, territorial structure resulting from the interaction between morphological features, agricultural aspects and attributes of the settlement system, which can be characterised or recognised in several contexts. The 23 rural morphotypes identified and mapped in the Region are linked to the description of their structural, functional, management, values and critical aspects, as well as of landscape quality objectives for the preservation and propagation of patrimonial assets.